2021
DOI: 10.3390/sym13060992
|View full text |Cite
|
Sign up to set email alerts
|

Handedness Development: A Model for Investigating the Development of Hemispheric Specialization and Interhemispheric Coordination

Abstract: The author presents his perspective on the character of science, development, and handedness and relates these to his investigations of the early development of handedness. After presenting some ideas on what hemispheric specialization of function might mean for neural processing and how handedness should be assessed, the neuroscience of control of the arms/hands and interhemispheric communication and coordination are examined for how developmental processes can affect these mechanisms. The author’s work on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 270 publications
(394 reference statements)
1
24
1
Order By: Relevance
“…Taking into account the above facts and in accordance with the proposal presented by Michel in his review [40], at least four basic methods of assessing human handedness can be distinguished. The first method is associated with the individual's narrative or self-identified handedness, e.g., "I'm right-handed/left-handed/mixed-handed" or "I use ambilateral hands".…”
Section: Hemispheric Asymmetries and Phenomenon Of Handednessmentioning
confidence: 66%
See 4 more Smart Citations
“…Taking into account the above facts and in accordance with the proposal presented by Michel in his review [40], at least four basic methods of assessing human handedness can be distinguished. The first method is associated with the individual's narrative or self-identified handedness, e.g., "I'm right-handed/left-handed/mixed-handed" or "I use ambilateral hands".…”
Section: Hemispheric Asymmetries and Phenomenon Of Handednessmentioning
confidence: 66%
“…A recent interesting large-scale (1,766,671 participants) genome-wide association study (GWAS) revealed that 48 genetic variants are statistically associated with different forms of self-identified handedness (41 left-handed and 7 mixed) [78]. However, as Michel indicated in his review [40], GWAS does not identify genes that are commonly found associated with handedness in other primate species or across different phases of human development, and these studies do not identify deep handedness homology. In addition, the author pointed out that genetics might have some influence on the initiation of the developmental trajectory of handedness, slightly affecting the probability of one form over another.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations